Camera trap survey of medium and large mammals in a montane rainforest of northern Peru - Jiménez, Carlos F. (2010)
Camera traps are a powerful tool for inventorying elusive and rare species and very useful to obtain ecologi- cal data for plans that involve wildlife conservation. In Peru, several surveys have been carried out in lowland Amazonia especially in the southeastern part of the country, but none in montane cloud forests or Yungas. We present the first camera trap studies produced in Peruvian Yungas at the locality of Querocoto village (Chota, Cajamarca), based on 2002 (dry season) and 1264 (wet season) camera traps-days (CTD). Two localities were surveyed in wet and dry season: The Pagaibamba Protection Forest and the San Lorenzo Forest. The wet season study was carried out in October and November, and the dry season in July to September of 2008. Eight mammalian species were recorded in both seasons. Some 66 (91.7%) independent records were obtained in the dry season, but only six (8.3%) in the wet one, suggesting a seasonality effect. The Mountain Paca Cunicu- lus taczanowskii was the most commonly photographed species, with 17.0 and 1.6 capture frequencies (dry and wet season respectively), whereas the Long-tailed weasel Mustela frenata (0.5 capture frequency in the dry season) was the most rare species. Activity patterns suggest that Mountain Paca C. taczanowskii and the Andean Skunk C. chinga are nocturnal, while Spectacled Bear T. ornatus and Tayra E. barbara are diurnal in the study area. Our records of the Ocelot Leopardus pardalis and the Tayra E. barbara are among the highest altitudinal records known for each species. In addition, the Anta Tapirus pinchaque was also identified by its tracks, representing one of the first record known south of the Huancabamba Depression.